Pesticide analysis in coffee leaves using a quick, easy, cheap, effective, rugged and safe approach and liquid chromatography tandem mass spectrometry: optimization of the clean-up step - Trevisan, Maria T.S.; Owen, Robert; Breuer, Andrea (Journal of chromatography, 2017)
An analytical method using a quick, easy, cheap, effective, rugged and safe (QuEChERS) procedure for multi-residue determination of 52 pesticides in coffee leaf extractshas been developed and validated according to SANTE/11945/2015 guidelines. Different sorbent combinations for dispersive solid phase extraction (d-SPE) clean-up as well as dispersive liquid-liquid microextraction (DLLME) were tested. The relative standard deviations (RSDs) for the recovery of 87-94% of pesticides added to coffee leaf extracts,was ≤20% for samples spiked at concentrations up to 50ng*g−1 depending on the clean-up procedures. However, samples spiked with a 100ng*g−1 pesticide mixture gave RSDs>20% for most pesticides when d-SPE was carried out adding Supelclean ENVI-Carb 120/400. To explain this fact,the secondary metabolic profile was analyzed in all the extraction and clean-up procedures. Only in the clean-up procedure with the addition of Supel QuE Z-Sep+, does caffeine show a constant adsorption between blank and spiked samples. In other clean-up procedures, the amount of caffeine was higher in those samples spiked with pesticides. This indicates competition between caffeine and pesticides for adsorption to the sorbent. Addition of Supel QuE Z-Sep+ to the procedure revealed only a 32% matrix effect, whereas using PSA+ C18 the matrix effect was close to 97%. The process efficiency is up to 54% with the addition of Supel QuE Z-Sep+ and just up to 7% for the other clean-up procedures. The method was successfully tested in coffee leaves from different types of cultivars. Pesticides were not detected in organic coffee leaf extracts, but thiametoxan was clearly detected in 50% of coffee leaf extracts harvested from coffee trees grown under traditional conditions as determined by UHPLC-TOFMSLC/QqTOF-MS/MS.